2023
DOI: 10.5267/j.uscm.2022.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supply chain organizational and supply agility on supply chain performance: The mediation role of supply chain strategy in retail shops

Abstract: This research aims to analyze the effect of supply chain organizational and supply agility on the performance of supply chain performance through the mediation role of the supply chain strategy in the retail industry. Retail business design creates novelty, it is very important for manufacturers to stay focused on producing goods. The presence of a retail shop will make it easier for consumers to get the goods and services they want. The research sample includes 180 companies or respondents. The results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 77 publications
(85 reference statements)
0
0
0
1
Order By: Relevance
“…Corporate governance (GCG) primarily aims to create a framework that ensures a company operates with transparency, accountability, and responsibility, thereby safeguarding the interests of shareholders and other stakeholders (Chouaibi et al, 2022). In efforts to reduce agency problems, GCG integrates principles such as the presence of independent directors, an audit committee responsible for monitoring financial reports and ensuring compliance with regulations, and attention to CEO and top executive management compensation structures (Riswandari et al, 2023). GCG has received increasing attention following financial crises and prominent corporate failures.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Corporate governance (GCG) primarily aims to create a framework that ensures a company operates with transparency, accountability, and responsibility, thereby safeguarding the interests of shareholders and other stakeholders (Chouaibi et al, 2022). In efforts to reduce agency problems, GCG integrates principles such as the presence of independent directors, an audit committee responsible for monitoring financial reports and ensuring compliance with regulations, and attention to CEO and top executive management compensation structures (Riswandari et al, 2023). GCG has received increasing attention following financial crises and prominent corporate failures.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In addition to regulatory compliance, GCG also involves ethical and integrity aspects in conducting business (Bobillo et al, 2018;Utami et al, 2021;Lubis, 2023). Riswandari et al (2023) asserted that their investigation revealed the intermediary function of the value chain, facilitating the impact of innovation strategies and corporate governance (GCG) on the operational performance of Indonesian manufacturing enterprises.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Sin embargo, las plazas de mercado analizan el efecto de la organización de la cadena de suministro y la agilidad de las adquisiciones del desempeño por medio de estrategias que sean innovadoras para estos rendimientos que deben presentar (Sutanto, et al, 2023). Es esencial, especialmente en la plaza de mercado de Facatativá para el éxito, determinar las oportunidades de mejora que tiene la cadena de suministro, lo que implica analizar los procesos actuales y determinar dónde se pueden realizar ajustes por medio de diagnósticos y diseños de herramientas de gestión para poder generar la eficiencia de las operaciones que están involucradas en la cadena de suministro (Reyes, et al, 2021).…”
Section: Introductionunclassified